Implementation Of Gianyar Regency Regional Regulation Number 7 Of 2014 On Smoke-Free Areas In Tourism Destination Regions (A Case Study of Ubud Tourism Village, Gianyar Regency) - I Made Darsana; Ida Ayu Putu Sri Widnyani; Nyoman Diah Utari Dewi (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
The implementation of Gianyar Regency Regional Regulation Number 7 of 2014 on Smoke-Free Areas (KTR) in Ubud Tourism Village is influenced by policy communication, resources, implementers’ disposition, and bureaucratic structure. Key issues include limited socialization with tourists and business owners, insufficient English-language signage, lack of enforcement officers, and the absence of designated smoking areas at major tourism spots. This study applied a descriptive qualitative approach using Edward III’s theory of implementation. Data were collected through interviews, observations, and document analyses. The findings indicate that KTR implementation remains suboptimal, as shown by frequent violations in markets, restaurants, and tourist attractions. Business owners are reluctant to warn tourists, inter-agency coordination is weak, and customary villages have not integrated KTR into local pararem activities. In conclusion, KTR implementation in Ubud remains largely normative and requires collaborative strategies among the government, customary villages, tourism actors, and the community to achieve healthier and smoke-free tourist areas.